Platform Comparison Between Games Console, Mobile Games And PC Games - Galehantomo P.S, Geraldus (Soegijapranata Catholic University, 2015)
In terms of platforms and game console, there are diffrences between, mobile games and pc gamesin the way it is used, the operator, the main event play, the game design and even the way the game work.We know that all the games on console platforms, PC and mobile, Â have their own characteristic which have advantages and drawbacksAll platforms compete to win the rating for the sake ofÂ their platform continuity. For rating, all games platforms develop games that are more qualified. Those games will determine the quality of the platforms, so that the game developers of each platform developtheir games maximally to compete.